MALAT1 shuttled by extracellular vesicles promotes M1 polarization of macrophages to induce acute pancreatitis via miR‐181a‐5p/HMGB1 axis. Issue 19 (27th August 2021) - Liu, Jie; Niu, Zequn; Zhang, Rui; Peng, Zhuo; Wang, Liming; Liu, Zhong; Gao, Yanxia; Pei, Honghong; Pan, Longfei
Abstract: Acute pancreatitis (AP) is a serious condition carrying a mortality of 25–40%. Extracellular vesicles (EVs) have reported to exert potential functions in cell‐to‐cell communication in diseases such as pancreatitis. Thus, we aimed at investigating the mechanisms by which EV‐encapsulated metastasis‐associated lung adenocarcinoma transcript‐1 (MALAT1) might mediate the M1 polarization of macrophages in AP. Expression patterns of MALAT1, microRNA‐181a‐5p (miR‐181a‐5p) and high‐mobility group box 1 protein (HMGB1) in serum of AP patients were determined. EVs were isolated from serum and pancreatic cells. The binding affinity among miR‐181a‐5p, MALAT1 and HMGB1 was identified. AP cells were co‐cultured with EVs from caerulein‐treated MPC‐83 cells to determine the levels of M1/2 polarization markers and TLR4, NF‐κB and IKBa. Finally, AP mouse models were established to study the effects of EV‐encapsulated MALAT1 on the M1 polarization of macrophages in AP in vivo. MALAT1 was transferred into MPC‐83 cells via EVs, which promoted M1 polarization of macrophages in AP. MALAT1 competitively bound to miR‐181a‐5p, which targeted HMGB1. Moreover, MALAT1 activated the TLR4 signalling pathway by regulating HMGB1. EV‐encapsulated MALAT1 competitively bound to miR‐181a‐5p to upregulate the levels of IL‐6 and TNF‐α by regulating HMGB1 via activation of the TLR4 signalling pathway, thereby inducing M1 polarization of macrophages in AP. In vivo experimental results also confirmed that MALAT1 shuttled by EVs promoted M1 polarization of macrophages in AP via the miR‐181a‐5p/HMGB1/TLR4 axis. Overall, EV‐loaded MALAT1 facilitated M1 polarization of macrophages in AP via miR‐181a‐5p/HMGB1/TLR4, highlighting a potential target for treating AP.